SIMBOLIK BHATARA SRI RAMBUT SEDANA DALAM USAHA DAGANG DI KOTA SINGARAJA (PERSEPEKTIF TEOLOGI HINDU) - Gede Mahardika (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
The beliefs of the Balinese Hindu community in the City of Singaraja towards BhataraSri Rambut Sedana in running a trading business can be seen from their daily activities andsymbols that are installed in every room or place that is used as a business. The formulation ofthe problem in this research is What is the symbolic form of Bhatara Sri Rambut Sedana inHindu Theology? This research plan was designed in the form of interpretive qualitative research.And the approach used, in this research plan using the ex post facto approach. The results of thisstudy are as follows, namely, the symbolic form of Bhatara Sri Rambut Sedana in Hindu theologyis wijudkan in the form of linggih daksina placed at the attachment of commercial businesses,offerings used in the worship of Bhatara Sri Rambut Sedana namely regulating blackmailers,burang canang fragrant , sesayut amertha sari / sari amertha, a slice of the colors and riversthat are offered to each of them.